(untitled) (Acta Scientiarum. Agronomy, 2018)
Numerical implementation methods such as the finite element method can be used in machine design to study the dynamic behavior of the plant. Input parameters for using the finite element method should be set based on the geometrical, physical and mechanical system under study. Thus, the aim of this study was to determine the mechanical properties of the rachis of macaw palm in the green maturation stage at an age of 180 days and at fruit maturation. The water content was calculated using the oven method of 105 ± 3°C for 24 hours. The modulus of elasticity for the rachis was determined by means of mechanical compression testing. The Poisson’s ratios were determined from the results of the longitudinal and transverse deformation of rachis test bodies. The shear tests were performed in two scenarios. In the first one, a blade was used without a tensioner, and in the second scenario, a blade was fixed with a tensioner, characterized by a chamfer at 45°. It was concluded that the modulus of elasticity of macaw palm rachis in the green maturity stage was higher than the values for the mature stage of ripeness.